Policy and Practice for Multilingual Educational Settings Comparisons across Contexts - Björklund, Siv (Bilingual Education & Bilingualism, 2023)
Exploring multilingualism as a complex, context-related, societal and individual phenomenon, this book centres around perspectives on how multiple languages are made (in)visible within educational settings in the Global North. The authors of each chapter compare and contrast findings across geographical contexts with the goal of understanding the facets of multilingualism that, on the one hand, conform across contexts, and on the other, diverge context-specifically. The chapters range from contributions with a focus on national/state planning for the development of sustainable multilingual and intercultural educational policies, to chapters that deal with multilingual practices and identities of students and student teachers as well as the consequences for language practices, strategies and policies in diversifying societies. This cross-contextual, comparative and interdisciplinary exploration of multilingualism will be of great interest to researchers, administrators, practitioners and students within the fields of multilingual education, sociolinguistics, youth culture and identity studies. The book is open access under a CC BY NC ND licence.